Pattern of Bacterial Culture in Intensive Care Unit of Holy Family Hospital, Rawalpindi - Farheen Khalid, Abdul Slam, Abdullah Ibn Munir, Azka Laraib, Imran Mehdi Haidry, Rana Muhammad Usman, Muhammad Mujeeb Hassan, Salman Wazir, Zarmeen Khalid, Farheen Khalid, Abdul Slam, Abdullah Ibn Munir, Azka Laraib, Imran Mehdi Haidry, Rana Muhammad Usman, Muhammad Mujeeb Hassan, Salman Wazir, Zarmeen Khalid (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Bacterial infections and related sepsis are very common in non-cardiac Intensive Care Units in the healthcare setup of Pakistan. They are one of the leading causes of death in ICUs. This study was conducted to determine the frequency of culture positive patients admitted to ICU of Holy Family Hospital according to age, gender, most common bacterial isolates cultured from different infection sites and their antibiotic sensitivity pattern. Methods: In this descriptive cross-sectional study, 352 indoor ICU patients’ data was taken from records of the ICU of Holy Family Hospital from the year 2009 to 2016. Collected data included the information regarding the site from where the sample was taken, culture positive microbes, and the antibiotic sensitivity of the bacterial isolates. Results: Over a period from year 2009 to 2016, cultures of 352 patients were included amongst whom 174 (49.4%) were males and 178 (50.6%) were females. 257 (73.0%) were culture positive while 95 (26.9%) showed no growth for any organism. Most frequently isolated organism was E. coli 90 (25.6%) followed by Pseudomonas 47 (13.4%), Methicillin Resistant Staphylococcus aureus (MRSA) 38 (10.8%), Klebsiella 38 (10.8%), Coliform 14 (4.0%), Acinetobacter 12 (3.4%), Enterobacter 6 (1.7%), Providencia 6 (1.7%) and Methicillin Resistant Staphylococcus epidermidis (MRSE) 6 (1.7%). Antibiotic sensitivity of the isolates showed that the predominant bacteria like Escherichia coli (E. coli), Pseudomonas and MRSA were most sensitive to Amikacin 39 (43.3%), Polymyxin B 19 (40%) and Vancomycin 23 (73.7%) respectively. Conclusion: The most common bacteria isolated were E. coli, Pseudomonas, Klebsiella, and MRSA showing sensitivity to Imipenem, Polymyxin B, SCF and Vancomycin.